THE IMPACT OF FINANCIAL RATIO ON THE MARKET VALUE OF MANUFACTURING FIRM IN INDONESIA - Chaidir, Randy; Langelo, Friska; Rompas, Debora Helen; Lumempouw, Eliska Gricy; Angel, Christania Graciella; Nayoan, Jeyfenshi (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
This study investigates the effects of liquidity, profitability, and solvency on firm value in companies listed on the Indonesia Stock Exchange. The research employs a quantitative approach using multiple regression analysis on a sample of 25 companies over the period 2020–2024. The findings reveal that liquidity does not significantly influence firm value, indicating that investors do not prioritize short-term financial flexibility when evaluating market valuation. Excessively high or low liquidity levels appear to have little impact on investor perceptions of the company’s worth. In contrast, profitability has a positive and significant effect on firm value. This highlights the critical role of earnings generation and operational performance in enhancing investor confidence and increasing market valuation. Profitability serves as a strong signal of efficient management and sustainable growth potential, making it the primary financial factor considered by investors. Additionally, solvency, which measures the company’s ability to meet long-term obligations, is found to have no significant effect on firm value. This suggests that, as long as companies manage long-term debt responsibly and maintain manageable financial risk, investors focus less on solvency when assessing firm value. Overall, the results imply that profitability is the most influential determinant of firm value, while liquidity and solvency are less impactful. The study contributes to corporate finance literature by providing empirical evidence on the relative importance of financial ratios in firm valuation and offers practical insights for managers to prioritize profitability improvement strategies to enhance firm value.